New sex attractants for 14 boreal forest moth species (Lepidoptera) - Kozlov, Mikhail V (Bulgaria, 2026)
Field screening was conducted in subarctic boreal forests of the central Kola Peninsula, northwestern Russia, using eight (Z)-monounsaturated aliphatic compounds associated with moth sex pheromones: (Z)-5-decenyl acetate, (Z)-7-dodecenyl acetate, (Z)-7-dodecen-1-ol, (Z)-5-tetradecenyl acetate, (Z)-7-tetradecenyl acetate, (Z)-9-tetradecenyl acetate, (Z)-11-hexadecenyl acetate, and (Z)-11-hexadecenal. These compounds were tested both singly and in binary combinations (in some cases at different ratios), yielding 26 lure types. A total of 260 traps, deployed from 17 July to 12 August 1993, captured 18 moth species: one Yponomeutidae, one Argyresthiidae, one Coleophoridae, one Crambidae, two Geometridae, and 12 Noctuidae species. For 14 of these species, this study provides the first information on attractive compositions of synthetic lures.